2001
DOI: 10.1159/000059343
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular characterization of de novo translocation t(8;14)(q22.3;q13) associated with a vascular and tissue overgrowth syndrome

Abstract: Klippel-Trenaunay syndrome (KTS) is a disorder primarily characterized by capillary-venous vascular malformations associated with altered limb bulk and/or length. We report the identification of a balanced translocation involving chromosomes 8q22.3 and 14q13 in a patient with a vascular and tissue overgrowth syndrome consistent with KTS. We demonstrated that translocation t(8;14)(q22.3;q13) arose de novo. These data suggest that a pathogenic gene for a vascular and tissue overgrowth syndrome (KTS) may be locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 19 publications
(18 reference statements)
1
32
0
1
Order By: Relevance
“…In several patients the balanced translocation involving chromosomes 8q22.3 a 14q13 was described and found, in others translocation t (5; 11), (q13.3; p15.1). Identifi cation of two different conversions of chromosomes connected with Klippel-Trenaunay syndrome probably means the portion of more genes, which indicates its genetic heterogeneity (7).…”
Section: Discussionmentioning
confidence: 99%
“…In several patients the balanced translocation involving chromosomes 8q22.3 a 14q13 was described and found, in others translocation t (5; 11), (q13.3; p15.1). Identifi cation of two different conversions of chromosomes connected with Klippel-Trenaunay syndrome probably means the portion of more genes, which indicates its genetic heterogeneity (7).…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5,11,13,16,28,30) Spinal AVMs account for 3-4% of all intradural spinal cord mass lesions, but conus medullaris-cauda AVMs are even rarer, sporadic, and mostly anecdotal. 31) There may be a possible association between KTS and spinal AVM as a result of an embryonic disorder that affects both the ventrolateral and dorsolateral arteries, and gives rise to segmental neurocutaneous angiomas.…”
Section: Discussionmentioning
confidence: 99%
“…8) New genetic insights in KTS pathogenesis have suggested that overexpression of VG5Q angiogenic factor and t(5;11)(q13.3;p15.1) translocation may result in increased angiogenesis. 28,30) However, KTS is genetically heterogeneous so the sporadic occurrence of the syndrome may be explained by predominant inheritance or autosomic-dominant inheritance with incomplete penetrance involving mutated genes that code for angiogenic factors. 1,5,11,28,30) Due to the sporadic incidence of KTS and to the even more rare KTS-spinal AVM association, further investigations are needed to validate the genetic hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous genetics studies have identified three chromosomal abnormalities in three separate KTS patients: two balanced translocations t(5.11)(q13.3;p15.1) and t (8,14)(q22.3;q13), and an extra supernumerary ring chromosome 18 (Tian et al 2004;Timur et al 2004;Wang et al 2001;Whelan et al 1995). Molecular characterization of KTS-associated translocation t(5.11)(q13.3;p15.1) advanced far ahead of the other two cytogenetic anomalies.…”
Section: Introductionmentioning
confidence: 98%